Structure-based design of human pancreatic amylase inhibitors from the natural anthocyanin database for type 2 diabetes. Issue 4 (27th March 2020) - Xie, Lianghua; Mo, Jianling; Ni, Jingdan; Xu, Yang; Su, Hongming; Xie, Jiahong; Chen, Wei
Abstract : Malvidin 3- O -arabinoside is identified as a novel human pancreatic amylase inhibitor from the natural anthocyanin database with a structure-based design approach. Abstract : Human Pancreatic Amylase (HPA) is an important target for prevention and treatment of type 2 diabetes. Acarbose is a currently available drug acting as a HPA inhibitor, but its gastrointestinal side-effects cannot be neglected. Thus, developing novel HPA inhibitors with no side-effects is of great importance. Herein, we adopted a structure-based design approach and discovered a potent HPA inhibitor, malvidin 3- O -arabinoside (M3A), from the natural anthocyanin database. We identified M3A as an effective HPA inhibitor through virtual screening, enzyme activity and enzyme kinetic assays. We reported the structure and activity relationships as both the anthocyanidin core and glucosyl group affected the HPA inhibitory effect of anthocyanins. Molecular dynamics studies indicated that the HPA inhibition of M3A occurred via its binding to the HPA key catalytic residues Arg195 and Asp197 through stable hydrogen bonding. In addition, M3A was found to reduce α-helix fractions and increase β-sheet fractions in CD spectrometry. Further in vivo studies showed that M3A significantly ameliorated the postprandial blood glucose level. Taken together, our results provide new insights into the development of novel HPA inhibitors from natural sources as food supplements for type 2 diabetes.